Delphi method as a didactic strategy in seedbed formation research - Quezada, Guillermo; Castro-Arellano, María del Pilar; Oliva, Juan; Gallo, Carlos; Quezada-Castro, María del Pilar (Revista Innova Educación, 2020)
The objective was to analyze the contribution of the Delphi method in the research seed formation process. The work was carried out under the qualitative approach, analytical method, explanatory design and document review technique. It was noted as a result that the aforementioned method should be considered as a didactic strategy because it contains formative, multidisciplinary, finalist and methodological feasibility, being necessary to promote it for the purpose of academic integration between senior and junior teachers. It is concluded that the aforementioned method encourages active participation in the teacher-student relationship and contributes to the training process as researchers from the university classrooms.